COMPARATIVE ANALYSIS OF SHARIA AND CONVENTIONAL STOCKS PORTFOLIO PERFORMANCE USING SHARPE, TREYNOR AND JANSEN METHODS - Muchlisina, Fanji; Riskayanto (The Islamic Education and Multiculturalism Foundation, 2023)
The Sharia capital market emerged as an alternative vehicle for the investor community to invest in the financial world in accordance with Sharia principles. As an alternative investment vehicle, the Sharia capital market is of course also targeted by investors who care about Sharia in addition to the general objective as a vehicle used to a profitable investing. Based on this basic framework, this research was conducted with the aim of analyzing and comparing stock performance in the form of stock portfolios between Sharia-based and conventional one. The JII70 stock index was used as an object for the Sharia stock portfolio, while the conventional stock portfolio was represented by the LQ45 index. The performance assessment used on these two portfolios was a portfolio performance assessment using the Sharpe, Treynor, and Jensen methods during the Covid-19 pandemic. The performance of these stock portfolios according to the three methods showed positive results. The performance of the JII70 stock portfolio was lower than the LQ45 index although it is insignificant. Meanwhile, according to the Treynor index, the performance of the JII70 was better than the LQ45 although it is insignificant.